154k views
1 vote
Can someone show me an example or a easy way to solve this.

Can someone show me an example or a easy way to solve this.-example-1

2 Answers

7 votes

Answer:

(-3/4)x + 2 y = (4/3)x + 2 y = (-4/3)x - 2 y = -3x + 8.

User Adam Casey
by
5.9k points
4 votes

Answer:

y=-3/4+2

Explanation:

3x+4y=8

-3x -3x

4y=-3x+8

/4 /4

y=-3/4+2

Hope this helped.

User Penleychan
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.